Exploring Trauma, Memory, and Identity Formation in ‘The School for Good Mothers’ by Jessamine Chan - Rouabhia, Ridha; Makhlouf, Amro (Indonesian Journal of English Language Studies (IJELS), 2025)
This article examines the links between trauma and memory and implications for identity in Jessamine Chan's novel, The School for Good Mothers. It describes how intergenerational trauma impacts Frida (the protagonist) and her interactions with Harriet from the respective perspectives of psychoanalytic trauma theory and pluralistic trauma models. Based on the analysis, Frida's identity and behaviours are significantly shaped by unresolved childhood trauma and social expectations related to motherhood. Hence, the novel critiques institutional approaches to dealing with trauma that rely on surveillance and standardisation as opposed to identifying and resolving deeper psychological issues. For example, the continued monitoring presented in the novel is a form of ongoing traumatisation and mirrors contemporary concerns about privacy, autonomy, and mental health. This research contributes to the field of trauma studies by focusing on trauma as a complexity of experiences based on individual experiences, traumatic experiences within family systems, and external societal pressures, particularly in the experiences of mothers. Lastly, this research illustrates, through multiple lenses, why trauma should be treated individually and how universalised approaches to trauma are limited at best when addressing complex trauma in institutional contexts.